2017
DOI: 10.3389/fphar.2017.00822
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII Requirement for in Vivo Insular Cortex LTP Maintenance and CTA Memory Persistence

Abstract: Calcium-calmodulin/dependent protein kinase II (CaMKII) plays an essential role in LTP induction, but since it has the capacity to remain persistently activated even after the decay of external stimuli it has been proposed that it can also be necessary for LTP maintenance and therefore for memory persistence. It has been shown that basolateral amygdaloid nucleus (Bla) stimulation induces long-term potentiation (LTP) in the insular cortex (IC), a neocortical region implicated in the acquisition and retention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Inhibition of aIC-to-BLA neurons using local CNO delivery at the aIC further confirmed the necessity of the projection for CTA memory acquisition and expression ( Fig. 5E-I ), while suggesting that its recruitment acts upstream of BLA collaterals to reward centers (Dunn and Everitt, 1988;Juárez-Muñoz et al, 2017;Inui et al, 2019). Nonetheless, it is possible that aIC collaterals of the projection to other regions might also contribute to the effects elicited by chemogenetic interventions (Wright and Groenewegen, 1996;Reynolds and Zahm, 2005;Stachniak et al, 2014).…”
Section: Discussionmentioning
confidence: 53%
“…Inhibition of aIC-to-BLA neurons using local CNO delivery at the aIC further confirmed the necessity of the projection for CTA memory acquisition and expression ( Fig. 5E-I ), while suggesting that its recruitment acts upstream of BLA collaterals to reward centers (Dunn and Everitt, 1988;Juárez-Muñoz et al, 2017;Inui et al, 2019). Nonetheless, it is possible that aIC collaterals of the projection to other regions might also contribute to the effects elicited by chemogenetic interventions (Wright and Groenewegen, 1996;Reynolds and Zahm, 2005;Stachniak et al, 2014).…”
Section: Discussionmentioning
confidence: 53%
“…A previous electrophysiological study showed that CTA learning enhances the functional connectivity between the IC and BLA [ 24 ]. In the IC, LTP is induced by the high frequency stimulation of BLA, which modulates CTA memory formation [ 18 22 ]. Recently, it is shown that IC-to-BLA projecting neurons are an essential components of the CTA acquisition and memory retrieval [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IC and BLA are reciprocally connected, and these interconnections are important for the retention of CTA memory [ 17 ]. It has also been shown that high frequency stimulation of the BLA induces long-term potentiation (LTP) in the IC, and the induction of LTP in the BLA-IC pathway before CTA training increases the retention of memory [ 18 22 ]. In addition, CTA training induces subsequent LTP in the BLA-IC pathway and increases amygdala-cortical function connectivity [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We next employed our scRNA-seq dataset of mouse hippocampus (from CAG-CreERT2-ODD::R26R-tdTomato mice) collected upon normoxia (21% O 2 ) versus inspiratory hypoxia (6% O 2 for six hours/day) for five consecutive days (compare Figure 1 b; GSE162079 [ 7 ]), to evaluate the hypoxia regulation of all cells expressing the CaMKIIα-promoter. In the first step, we selected all glutamatergic neuronal populations (including mossy fiber cells), known to express CaMKIIα [ 12 , 13 , 14 , 15 ] from the hippocampal dataset and compared the expression levels of CaMKIIα under normoxic and hypoxic conditions ( Figure 6 a). Surprisingly, CaMKIIα was consistently upregulated under hypoxia in the excitatory neurons from the three discernible hippocampal regions (CA1, CA3, dentate gyrus).…”
Section: Resultsmentioning
confidence: 99%